Analysis of Reading Difficulties of High-Class Students at State Elementary School 01 Sumi - Ningsi, Ruri; Haryanto, Lutfin; Suryaningsih, Sri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The study aims to analyze the reading difficulties of high school students in state elementary school 01 Sumi and identify the factors causing the reading difficulties that occur. The method uses data collection, observation and interviews. The type of research used is qualitative research. Data were taken from 79 high school students, with the results of the study 5 categories of students with reading difficulties in high class. The category of very good at reading consists of 10 students, the category of able to read consists of 17 students, the category of quite good at reading consists of 29, the category of less able to read consists of 15 students, and the category of unable to read consists of 8 students. The reading difficulties experienced in these 5 categories are difficulty in understanding the meaning of the reading text, difficulty in recognizing the alphabet, difficulty in distinguishing vowels and consonants, difficulty in recognizing punctuation, difficulty in comparing the contents of the reading, difficulty in making conclusions, difficulty in distinguishing factual and opinion sentences, difficulty in distinguishing main ideas from the details presented. There are several factors causing the reading difficulties experienced: 1. Lack of early literacy of students, 2. The role of parents, 3. Interest and motivation, and 4. Social environment.